Knowledge, Attitude and Practice of Cancer Screening Among Women in Tamil Nadu, Southern India - A Qualitative Study - Sundar, Jasmine S; Srijayanth S, Parameswari; Karthikeyan, P R; A S, Hemapriya; S, Valarmathi; Kalpana, Kalpana; Paul A, Arul; K, Narayanasamy; G, Srinivas (Asian Pacific Journal of Cancer Biology, 2025)
Background: Breast and cervical cancers represents major public health challenges globally, with considerable impact on women’s health in India. Early detection through screening plays a critical role in improving survival rates and treatment outcomes. Understanding the knowledge, attitudes, and practices surrounding cancer screening is essential to develop effective, targeted interventions that can improve uptake and reduce the burden of these diseases. This study aims to explore these factors among women in Chennai, including both those diagnosed with cancer and non-cancer participants. Methods: This qualitative KAP study, conducted between October 2021 and May 2022, involved 189 purposively sampled women (with and without breast/cervical cancer) across five tertiary care institutions in Chennai. Thirteen Focus Group Discussions (FGDs) were conducted to assess participants’ knowledge of cancer and screening, explore their attitudes toward prevention and early detection, and document their screening practices. Audio recordings were transcribed and analyzed using descriptive content analysis. Results: The findings revealed a generally low level of awareness, widespread misconceptions, and a diminished perception of personal risk, contributing to negative attitudes toward screening. However, screening behaviors were positively influenced by strong social support from peers and family, as well as by trusted media sources indicating these factors may help overcome some attitudinal barriers. Conclusion: Despite limited awareness and prevailing misconceptions, leveraging social support networks and accessible media presents a key opportunity for improving screening uptake. Public health initiatives should focus on strengthening knowledge, correcting misconceptions, and utilizing existing social and communication networks to enhance women’s participation in cancer screening programs.